PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN ULAR TANGGA TEMATIK (UTATIK) TERHADAP PEMAHAMAN KONSEP TEMA 8 SUBTEMA 3 KELAS V SEKOLAH DASAR - Febriana, Anis; Fakhriyah, Fina; Ardianti, Sekar Dwi (STKIP Persada Khatulistiwa Sintang, 2024)
The research aims to find out whether there is an influence of using the problem based learning model assisted by thematic snakes and ladders (UTATIK) on understanding the concept of theme 8 subtheme 3 at class V SD 4 Karangbener. Experimental research was conducted at SD 4 Karangebener with 20 students at class V as the research subjects. The data collection technique is a test technique with pretest and posttest instruments. The data analysis technique is a paired sample t-test using SPSS16. The research results show that the sig.(2-tailed) value of 0.000 is less than the significance level of 0.05 with an average pretest value of 42.38 and posttest 79.43, meaning that Ho is rejected and Ha is accepted. So it can be concluded that there is a significant influence of the problem based learning model assisted by thematic snakes and ladders (UTATIK) on understanding the concept of theme 8 subtheme 3 at class V SD 4 Karangbener.